(untitled) (TAJ: Journal of Teachers Association, 2019)
Background: Acute respiratory infections (ARI) include upper respiratory tract infections and lower respiratory tract infections. Infections of the respiratory tract are perhaps the most common human ailment. While they are a source of discomfort, disability and loss of time for most adults, they are a substantial cause of morbidity and mortality in young children. ARI may cause inflammation of the respiratory tract anywhere from nose to alveoli, with a wide range of combination of symptoms and signs. ARI in children is most common among others because heir constant contact with other kids who could be virus carriers. Children often don’t wash their hands regularly. They are also more likely to rub their eyes and put their fingers in their mouths, resulting in the spread of viruses. For prevention of malnutrition and infection of child breast feeding is an important determinant of child health in the prevention of malnutrition and infection but in many cultures other food was introduced years before the cessation of breast feeding. In Bangladesh, many infectious diseases such as diarrhoea and acute respiratory infections are the main cause of mortality and morbidity in infants aged less than one year. The importance of breast feeding in the prevention of infectious diseases during infancy is well known. Objective: In this study our main objective is to evaluate the association between ARI of infant and weaning status of infants admitted in selected Hospitals of Rajshahi. Study place and Method: This study provided a wide range of information regarding ARI and weaning status of infants admitted in selected hospitals of Rajshahi and from the surroundings. This was a case control type of study. A total of 230 caregiver or mothers were interviewed. Result & discussion: It was found that the relationship between weaning status of infants and occurrence of ARI was statistically significant (p<0.001). It was showed that majority of the babies of the case group were weaned by Cow’s milk and within the control group by mashed rice. The association between occurrence of ARI and type of weaning food was statistically significant (p<0.001). It was also found that majority of the babies living in rural areas developed ARI and also within the case group majority (29.6%) of the babies who were not exclusively breast fed developed ARI and the association between occurrence of ARI and EBF was statistically significant (p<0.001). Conclusion: Our study suggests that proportion of ARI is more among the infants who were weaned earlier. TAJ 2019; 32(1): 70-81